Process simulation and economic feasibility of biodiesel production from acid oil, a by-product of glycerol acidulation - Myint, Ni Ni; Thanapimmetha, Anusith; Saisriyoot, Maythee; Chiarasumran, Nutchapon; Srinophakun, Thongchai Rohitatisha; Gozan, Misri; Srinophakun, Penjit (Agriculture and Natural Resources, 2023)
Importance of the work: A new approach was investigated using acid oil from acidulation for its economic feasibility in biodiesel production. Objectives: To investigate the esterification conditions of biodiesel production from acid oil, and conduct process simulation and cost investigation using the ASPEN software. Materials & Methods: Reaction time (1–6 h) and the methanol-to-oil molar ratio (20:1–30:1) were varied with a fixed 4% H2SO4 catalyst at, 60 °C and 500 revolutions per minute. Based on the experimental data, the optimized conditions determined using the Minitab-17 software were used in the ASPEN process simulation. Then, the economic feasibility and sensitivity analysis were examined. Results: The acid oil comprised 33.63% free fatty acid, 72.36% fatty acid methyl ester and 1.3% water. After esterification using an acid catalyst, Minitab determined the optimum conditions of biodiesel production from the acid oil at 3.4 h reaction time and a 25.9:1 methanol-to-oil ratio, which produced biodiesel containing fatty acid methyl ester of 96.8% and free fatty acid of 0.32%. Consequently, 26,579.5 kg/d biodiesel were produced from 27,300 kg/d acid oil and 30,903 kg/d methanol, with 95% conversion. Finally, the project was economically feasible based on the net present value (USD 34,092,719), the internal rate of return (56%), the payback period (5.1 yr) and the production cost (USD 0.77/L). Main finding: Acid oil could be used as new raw material for biodiesel production. The results showed that the production process was economically suitable for investment. Minitab was a helpful tool for optimization, while ASPEN was excellent for process simulation and economic assessment.